2019
DOI: 10.12669/pjms.36.icon-suppl.1709
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Vertebral Fractures in Patients presenting with Hip Fractures

Abstract: Objective: To determine the frequency of vertebral fractures in patients presenting with hip fractures. Methods: This prospective study was conducted at The Indus Hospital, Karachi, from May 2018 to November 2018. All patients above 40 years presenting with hip fractures were enrolled and a dorsal lumbar lateral view radiograph was obtained to investigate for vertebral fractures. Data was entered and analyzed using SPSS. Post-stratification, Chi-square/Fisher exact test was applied as appropriate to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Our findings were comparable to that of Sadat-Ali et al [ 15 ], who reported a vertebral fracture in 24.7% of the patients in Saudi Arabia. Gallacher et al and Chinoy and Javed also found that 25% of patients presenting with non-vertebral fracture also had a simultaneous, asymptomatic vertebral fracture [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were comparable to that of Sadat-Ali et al [ 15 ], who reported a vertebral fracture in 24.7% of the patients in Saudi Arabia. Gallacher et al and Chinoy and Javed also found that 25% of patients presenting with non-vertebral fracture also had a simultaneous, asymptomatic vertebral fracture [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in cases of osteoporosis in elderly people is one of the major reasons for hip fracture. 1 Mortality rates between 20-30% are reported due to the femur injury and the mortality rate in the elderly patients is expected to increase in the next 20 years. 2 A large number of cases of hip fracture shake the healthcare system and the economy.3 Surgical intervention is only option for treating neck of femur fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality during the perioperative period and one year after surgery is extremely high at 33%. Relative animal experiments have revealed that more new bone tissues are generated after mesenchymal stem cells implantation in the site of osteoporosis, trabecular density of the local new bone increases, and the bone tension test results are improved, which is helpful to increase the local bone density [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%